2021
DOI: 10.1111/acv.12746
|View full text |Cite
|
Sign up to set email alerts
|

Low hatching success in the critically endangered kākāpō is driven by early embryo mortality not infertility

Abstract: In many endangered species, reproductive failure is a major barrier to recovery. The critically endangered kākāpō Strigops habroptilus exemplifies this challenge: 61% of their eggs fail to hatch, and of these 73% show no sign of development. Undeveloped eggs have previously been attributed to male infertility, but recent studies of non-threatened bird species suggest fertilisation failure is rare in the wild. The underlying causes of fertilisation failure and embryo death differ, so distinguishing between them… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
18
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(19 citation statements)
references
References 39 publications
(47 reference statements)
1
18
0
Order By: Relevance
“…This was conducted either in the nest or in an incubation facility, and was sufficient for detecting development from approximately four days after laying. Microscopic methods can detect earlier development ( Savage et al, 2021 ), but these have only been conducted for a single breeding season for kākāpō, and so could not be used in the current study which spans multiple years. As a result of using ‘apparent’ rather than true fertility in our analyses, approximately a quarter of the eggs in which embryos died at a very young age (before four days) will have instead been classed as infertile ( Savage et al, 2021 ).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…This was conducted either in the nest or in an incubation facility, and was sufficient for detecting development from approximately four days after laying. Microscopic methods can detect earlier development ( Savage et al, 2021 ), but these have only been conducted for a single breeding season for kākāpō, and so could not be used in the current study which spans multiple years. As a result of using ‘apparent’ rather than true fertility in our analyses, approximately a quarter of the eggs in which embryos died at a very young age (before four days) will have instead been classed as infertile ( Savage et al, 2021 ).…”
Section: Methodsmentioning
confidence: 99%
“…A primary reason for low productivity in kākāpō is the high rate of infertility. Approximately 40% of kākāpō eggs are considered infertile from visual inspection (‘candling’), although a recent fluorescence microscope study showed that 72% of these ‘apparently infertile’ kākāpō eggs were actually fertile, and instead failed due to very early embryo death ( Savage et al, 2021 ).…”
Section: Introductionmentioning
confidence: 99%
“…In some contexts, exposing extremely rare threatened species to invasive predators would be too risky, and full control/eradication/exclusion of invasive predators should remain the goal. For example, the entire population of k ak ap o (Strigops habroptilus), a large, flightless, nocturnal parrot formerly common in New Zealand (Savage et al, 2021), consists of only 199 individuals (May 2022, NZ DOC, 2022). Increasing the k ak ap o's population has been a considerable challenge due to its irregular and distinctive breeding patterns and high level of reproductive failure (Elliott et al, 2001;Savage et al, 2021).…”
Section: Long-term Thinkingmentioning
confidence: 99%
“…For example, the entire population of k ak ap o (Strigops habroptilus), a large, flightless, nocturnal parrot formerly common in New Zealand (Savage et al, 2021), consists of only 199 individuals (May 2022, NZ DOC, 2022). Increasing the k ak ap o's population has been a considerable challenge due to its irregular and distinctive breeding patterns and high level of reproductive failure (Elliott et al, 2001;Savage et al, 2021). Exposing this species to predation, with its population size at such critical levels, would obviously be irresponsible.…”
Section: Long-term Thinkingmentioning
confidence: 99%
“…Having undergone severe population bottlenecks, kākāpō are now highly inbred and suffer from low reproductive success, which is further compounded by their sporadic breeding which only occurs during heavy podocarp mast seasons (approx. every 2 - 4 years) [Merton et al 1984; Powlesland et al 1992; Elliott et al 2001; Eason et al 2006; Savage et al 2021]. However, recent findings suggest that despite their long-term small population size, kākāpō have a reduced number of harmful mutations than expected [Dussex et al 2021].…”
Section: Introductionmentioning
confidence: 99%